The relationship between the family and the school and the prospects of cooperation in the upbringing of children - Maani Ali AL-Saedi, Antisar (Al-Adab Journal, 2019)
The family plays an essential role in the behavior of individuals in a way that is both normal and abnormal. The behavioral models provided to their children are the first social institution that nurtures, protects and satisfies the child’s biological and psychological needs, which help him to move from his biological state to his social status, so that he can rely on himself in his affairs. Private and public and able to conform to the demands and values ​​of society. The family is an essential necessity for the survival of the human race and the continuation of social existence. The family has been and remains the most powerful social institution that affects all material and moral gains of man. The school is a social institution which is no less important than the family. The goals are one and the roles are complementary. Which each institution seeks to form and normalize in a way that creates a good citizen. Both the school and the family have a complementary role. The relationship between the family and the school must be based on the principles of cooperation, communication, mutual interaction and effective partnership. And the means and means to activate this relationship at the level of application and practice, and remains the school is to take the first step towards this openness and must work hard to make the family join and share the concerns of work, and must be open to the rest of the components of the ocean by activating all Legislative and legal measures that enable it to achieve this openness.